Is Heparin the Ideal Anticoagulant for Cardiopulmonary Bypass? Dermatan Sulphate May Be an Alternate Choice - Brister, Stephanie J; Ofosu, Frederick A; Heigenhauser, George J F; Gianese, Francesco; Buchanan, Michael R (Thrombosis and Haemostasis, 1994)
Performance of cardiopulmonary bypass (CPB) during cardiac surgery requires the administration of high dose heparin to prevent CPB pump occlusion. However, this heparin use is associated with bleeding side-effects. Moreover, at the end of CPB, the heparin must be neutralized with protamine sulphate, which is also associated with adverse side-effects. A number of recent studies suggest that dermatan sulphate may be useful as an alternate anticoagulant to heparin. We determined whether CPB could be performed using dermatan sulphate instead of heparin, in an adult pig CPB model. When heparin was used, a high dose (> 200 U/kg, which generated > 3 anti-thrombin U/ml of plasma), was required to perform successful CPB and to maintain CPB pump patency. This dose was associated with a post CPB bleeding of ≈ 600 ml/2h. in contrast, successful CPB could be achieved when the pigs were given lower doses of dermatan sulphate than heparin, which in turn, were associated with less bleeding. We conclude that dermatan sulphate may be an alternate anticoagulant for cardiac surgery